Lithium-Sulfur Batteries: Electrochemistry, Materials, and Prospects - Yin, Ya-Xia; Xin, Sen; Guo, Yu-Guo; Wan, Li-Jun (Angewandte Chemie International Edition, 2013)
With the increasing demand for efficient and economic energy storage, Li‐S batteries have become attractive candidates for the next‐generation high‐energy rechargeable Li batteries because of their high theoretical energy density and cost effectiveness. Starting from a brief history of Li‐S batteries, this Review introduces the electrochemistry of Li‐S batteries, and discusses issues resulting from the electrochemistry, such as the electroactivity and the polysulfide dissolution. To address these critical issues, recent advances in Li‐S batteries are summarized, including the S cathode, Li anode, electrolyte, and new designs of Li‐S batteries with a metallic Li‐free anode. Constructing S molecules confined in the conductive microporous carbon materials to improve the cyclability of Li‐S batteries serves as a prospective strategy for the industry in the future. Electrochemical cells with high energy densities are of great importance to satisfy the urgent demand for electronic vehicles and electricity storage. The Li‐S battery is one promising candidate, yet it suffers from the low utilization of active materials and poor cycle stability. The electrochemistry and challenges facing Li‐S batteries is addressed, and recent progress of materials related to Li‐S batteries is summarized.